2016
DOI: 10.1111/jpy.12443
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and decadal patterns in Discostella (Bacillariophyceae) species from bi‐weekly records of two boreal lakes (Experimental Lakes Area, Ontario, Canada)

Abstract: A recent rise in the relative abundance of Discostella species (D. stelligera and D. pseudostelligera) has been well documented from sedimentary diatom assemblages across the Northern Hemisphere. This unprecedented change over the last ~150 years has been linked to rises in atmospheric temperatures, changes in ice cover, and/or increases in thermal stability, among other factors. The bi-weekly monitoring data from two boreal lakes at the Experimental Lakes Area (ELA) in northwestern Ontario were analyzed acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The same pattern was observed for L. bodanica, even though mixing depths showed only small differences across the two ice-out years. Boeff et al [18] also found that D. stelligera was more abundant in some Maine lakes in late ice-out years, in contrast to the early ice-out patterns found in some other areas [14,17]. The effects of the complex interactions between light and nutrients on Cyclotella taxa are well known and reviewed by Saros & Anderson [72], and are likely behind the weaker links between thermal structure and taxon responses in this boreal lake compared to those observed in Arctic lakes.…”
Section: Discussionmentioning
confidence: 96%
“…The same pattern was observed for L. bodanica, even though mixing depths showed only small differences across the two ice-out years. Boeff et al [18] also found that D. stelligera was more abundant in some Maine lakes in late ice-out years, in contrast to the early ice-out patterns found in some other areas [14,17]. The effects of the complex interactions between light and nutrients on Cyclotella taxa are well known and reviewed by Saros & Anderson [72], and are likely behind the weaker links between thermal structure and taxon responses in this boreal lake compared to those observed in Arctic lakes.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, variable seasonal patterns have been observed in some other boreal lakes (Boeff et al 2016;Wiltse et al 2016), although we note that the ice-covered period has been ignored in most previous studies, making conclusions about seasonality incomplete. Because the physical drivers examined in this study affect lakes throughout the boreal region, many of the general processes observed in this study should be able to inform interpretations of sediment diatom records in a wide variety of lakes, although specific drivers are likely to be more or less important in individual lakes.…”
Section: Consequences For Interpreting the Sedimentary Diatom Recordmentioning
confidence: 81%
“…Early spring runoff may also increase nutrient availability under ice through the lateral dispersion of solutes into the stratified under ice surface layer, in contrast to a flush through the system within a more rapid spring flood (Cortés et al 2017;Jeppesen et al 2009). Other recent studies have also identified a relationship between warm early-spring conditions and the increased prevalence of C. glomerata (Wiltse et al 2016) although the mechanisms hypothesized to explain the observed trends were somewhat incomplete, in part because continuous measurements were not made throughout the winter period.…”
Section: Seasonal Cyclesmentioning
confidence: 92%
See 2 more Smart Citations